Subgroup analysis of investment constraints: Evidence from Ugandan microenterprises - Helke Seitz (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Most microenterprises barely grow beyond subsistence level, as profitable investments are not realized due to barriers like credit, savings, and managerial constraints. Using panel data, this study identifies subgroups that would benefit by an intervention aiming to alleviate constraints. Two obstacles are associated with lower investments: saving with others and no record keeping. Analyzing the effects for subgroups shows that for lower and medium educated, both obstacles are associated with lower investments. The analysis does not allow for drawing causal conclusions, results underpin that interventions aiming to reduce savings or managerial constraints could be effective when targeting the correct subgroups.
Keywords: D22; D25; O12; O16; 330; Entrepreneurship; Investment; Credit Constraints; Savings Constraints; Managerial Constraints